(untitled) - Branden, Carl (Oxford, 2001)
Written in a clear and engaging style, and profusely illustrated with superb computer graphics, Introduction to Protein Architecture is a textbook for second and third year undergraduate students and beginning post-graduate students, and will be of interest to all biological and medical scientists whose work touches on proteins.
Keywords: Proteins,Chất đạm; Structure,Cấu trúc